2012
DOI: 10.1111/j.1528-1167.2012.03495.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of fenfluramine as an add‐on treatment for Dravet syndrome

Abstract: Summary Purpose:  Despite the development of new antiepileptic drugs, Dravet syndrome frequently remains therapy resistant and is a catastrophic epilepsy syndrome. Fenfluramine is an amphetamine‐like drug that has been used in the past as a part of antiobesity treatments. Because of the possible cardiac adverse effects (valve thickening, pulmonary hypertension) associated with use of fenfluramine, it was withdrawn from the market in 2001. In Belgium, a Royal Decree permitted examination of the potential antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
176
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(194 citation statements)
references
References 48 publications
12
176
0
6
Order By: Relevance
“…CBD exhibits reasonable affinity at plausible concentration for 5-HT 1A and 5-HT 2A receptors, and 5-HT 2A receptors act as a target for fenfluramine, a drug for which some evidence exists supporting efficacy in drug-resistant epilepsies such as Dravet syndrome [144]. A very limited number of studies have reported changes in 5-HT receptor expression and function in people with epilepsy, although it remains unclear whether this is a consequence of the disease or a component of pathogenesis.…”
Section: Cbd Receptor Targets In Epilepsymentioning
confidence: 99%
“…CBD exhibits reasonable affinity at plausible concentration for 5-HT 1A and 5-HT 2A receptors, and 5-HT 2A receptors act as a target for fenfluramine, a drug for which some evidence exists supporting efficacy in drug-resistant epilepsies such as Dravet syndrome [144]. A very limited number of studies have reported changes in 5-HT receptor expression and function in people with epilepsy, although it remains unclear whether this is a consequence of the disease or a component of pathogenesis.…”
Section: Cbd Receptor Targets In Epilepsymentioning
confidence: 99%
“…Retrospective data Ceulemans and colleagues reported on the effect of fenfluramine in 12 patients with Dravet syndrome [Ceulemans et al 2012], retrospectively analyzed in 2010. The patient population included five patients from a study reported by Boel and Casaer [Boel and Casaer, 1996] who after review of their files and genetic testing were diagnosed with Dravet syndrome.…”
Section: Fenfluramine In Dravet Syndromementioning
confidence: 99%
“…In 2012, 12 patients were included of which 10 from the retrospective study and two new patients. Of the seven of 10 patients from the retrospective study [Ceulemans et al 2012] who had been seizurefree in the year prior to the initiation of this prospective study, four have continued to be free of seizures and three have exhibited rare seizure episodes (3-7 tonic-clonic convulsions) during the two additional years of observation. In three of them there was a provocative factor like fever, a stressful situation or intensive physical exercise explaining the seizures.…”
Section: Prospective Datamentioning
confidence: 99%
“…Lamotrigine can also cause seizure exacerbation,10 although has been reported to be beneficial in some cases 11. Effective treatment strategies include valproic acid, clobazam, topiramate, levetiracetam, fenfluramine and bromides,12, 13, 14 or dietary therapies (ketogenic or modified Atkins diet) 15. There are ongoing studies on the use of cannabidiol in children with DS 16.…”
Section: Introductionmentioning
confidence: 99%